National Politics Dr. Soetomo for Education in Indonesia: An Alternative to Strengthen the Pillars of Education - Kusnadi Kusnadi; Siti Utami Dewi Ningrum (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2024)
This article discusses the important role of national politics in strengthening the pillars of education, focusing on the views and contributions of Dr. Soetomo, an Indonesian national figure who played a key role in the independence movement. This article aims to explain how the national politics promoted by Dr. Soetomo can be a relevant alternative to strengthen the education system in the Indonesian context. The method used in this research is a qualitative approach with a literature study method. Dr. Soetomo emphasized the importance of forming character, ethics, and national values to strengthen the education pillar. This article describes how the principles of national politics can be applied in the formation of curriculum and teaching, and how this can influence students' intellectual and emotional development. In conclusion, this article highlights the central role of national politics in strengthening national education, by discussing the views and contributions of Dr. Soetomo as a relevant alternative to advance the pillars of education in Indonesia. Education based on national values, equality, and inclusiveness can help create a young generation with a strong national identity that is ready to face future challenges.